2021
DOI: 10.1002/biot.202000452
|View full text |Cite
|
Sign up to set email alerts
|

Pairing of orthogonal chaperones with a cytochrome P450 enhances terpene synthesis in Saccharomyces cerevisiae

Abstract: The supply of terpenes is often limited by their low extraction yield from natural resources, such as plants. Thus, microbial biosynthesis has emerged as an attractive platform for the production of terpenes. Many strategies have been applied to engineer microbes to improve terpene production capabilities; however, functional expression of heterologous proteins such as cytochrome P450 enzymes (P450s) in microbes is a major obstacle. This study reports the successful pairing of cognate chaperones and P450s for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To overcome this obstacle, chaperone-assisted expression systems have been extensively employed to improve the expression of heterologous proteins such as CYP450s. Kim et al demonstrated that the successful pairing of cognate chaperones with CYP450s could facilitate functional assembly of the PPD biosynthesis pathway [ 78 ]. When coexpression of cognate chaperones was coupled to the expression of PPD biosynthesis enzymes from P. ginseng , PPD production increased significantly by more than 2.5-fold.…”
Section: Sustainable Production Of Ginsenosides By Synthetic Metaboli...mentioning
confidence: 99%
“…To overcome this obstacle, chaperone-assisted expression systems have been extensively employed to improve the expression of heterologous proteins such as CYP450s. Kim et al demonstrated that the successful pairing of cognate chaperones with CYP450s could facilitate functional assembly of the PPD biosynthesis pathway [ 78 ]. When coexpression of cognate chaperones was coupled to the expression of PPD biosynthesis enzymes from P. ginseng , PPD production increased significantly by more than 2.5-fold.…”
Section: Sustainable Production Of Ginsenosides By Synthetic Metaboli...mentioning
confidence: 99%